Living in a Fluctuating Environment Increases Tolerance to Marine Heatwaves in the Free-Living Coralline Alga Phymatolithon lusitanicum - Schubert, Nadine; Santos, Rui; Silva, João (Frontiers in Marine Science, 2021)
Recently, increased attention is being paid to the importance of environmental history in species’ responses to climate-change related stressors, as more variable and heterogeneous environments are expected to select for higher levels of plasticity in species tolerance traits, compared to stable conditions. For example, organisms inhabiting environments with highly fluctuating thermal regimes might be less susceptible to the increasing frequency and intensity of marine heatwaves (MHWs). In this study, we assessed the metabolic and calcification responses of the rhodolith-bed forming Phymatolithon lusitanicum, from a coastal region that is strongly influenced by frequent changes between upwelling and downwelling conditions, to a simulated MHW scenario, with and without prior exposure to a moderate thermal stress. This allowed determining not only the influence of the species’ long-term thermal history on its resilience against MHWs, but also the rhodoliths capacity for short-term thermal stress memory and its importance during posterior MHW-exposure. Our findings indicate that the rhodoliths experienced negative impacts on daily net primary production (DNP) and calcification (DNC) during the MHW. The effect on the former was only temporary at the beginning of the MHW, while DNC was highly impacted, but exhibited a quick recovery after the event, suggesting a high resilience of the species. Furthermore, prior exposure to a moderate temperature increase, such as those occurring frequently in the natural habitat of the species, mitigated the effects of a subsequent MHW on DNP, while promoting a faster recovery of DNC after the event. Thus, our findings (1) support the hypothesis that benthic organisms living in nearshore habitats may benefit from the natural short-term temperature fluctuations in these environments with an increased resistance to MHW impacts and (2) provide first-time evidence for thermally induced stress memory in coralline algae.